Penerapan Teori Belajar Humanistik Pada Anak Usia DiniDalam Bingkai Iman Kristen - Tupamahu, Gloria; Arifianto, Yonatan Alex; Triposa, Reni (Jurnal Lentera Nusantara, 2023)
The main function of early childhood education is to be a place for children to process to develop themselves through their world, namely play. The state of the times and its development began to affect the perspective of thinking that in early childhood education institutions more applied play and learning. But nowadays early childhood education institutions are no longer playing while learning but have emphasized learning like elementary school children. Such things as children being forced to accept teaching that is not in accordance with their age is clearly not humanizing because the world of children is a world of play. Using a descriptive qualitative method, it can be concluded that in education, children are expected to feel freedom and also feel unbound by the opinions of other people, both educators and people in the scope of the child's own life, and students are also expected to be able to manage their own personalities with a sense of responsibility without violating existing moral and ethical rules. And where the achievement of humanistic learning in the realm of Christian Religious Education is to shape the child's personality so that the child achieves a change in attitude and is able to become a light in the community. The application of humanistic learning theory in early childhood in the frame of Christian faith can produce experiences that are holistic. with a focus on the needs and potential of children.AbstrakFungsi utama pendidikan anak usia dini adalah menjadi suatu wadah bagi anak untuk berproses mengembangkan dirinya melalui dunia mereka yaitu bermain. Keadaan zaman dan perkembangannya mulai memengaruhi perspektif berpikir yang pada lembaga pendidikan anak usia dini lebih diterapkan bermain dan belajar. Namun dewasa ini lembaga pendidikan anak usia dini bukan lagi bermain sambil belajar tetapi sudah menekankan belajar seperti layaknya anak sekolah dasar. Hal demikian seperti anak dipaksa untuk menerima pengajaran yang tidak sesuai dengan umurnya jelas tidak memanusiakan karena dunia anak adalah dunia bermain. Mengunkan metode kualitatif deskritif maka dapat disimpulkan bahwa Dalam Pendidikan anak diharapkan merasakan kebebasan dan juga merasakan ketidak terikatan oleh pendapat orang lain baik pendidik maupun orang-orang yang ada dalam lingkup kehidupan anak itu sendiri, dan anak didik juga diharapkan dapat mengatur kepribadian mereka sendiri dengan penuh rasa tanggung jawab tanpa melanggar aturan moral dan etika yang ada. Dan di mana capaian pembelajaran humanistik di ranah Pendidikan Agama Kristen untuk membentuk pribadi anak sehingga anak tersebut mencapai perubahan sikap dan mampu menjadi terang di dalam lingkungan Masyarakat. Penerapan teori belajar humanistik pada anak usia dini dalam bingkai iman Kristen dapat menghasilkan pengalaman yang bersifat holistik. dengan fokus pada kebutuhan dan potensi anak.